GRAVES’ DISEASE WITH OSCILLATING THYROID FUNCTION - Zakaria, Noorzeehan; Halim, Muhamad Hanif Bin Md; Lee, Yee Lin (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Oscillating thyroid status between hyper-and hypothyroidism in Graves’ disease is a rare phenomenon. The change in the thyroid status is likely attributed to the simultaneous presence of both thyroid-stimulating autoantibodies (TSAbs) and TSH-blocking autoantibodies (TBAbs) in an individual. CASE We report the case history of a 14-year-old female who presented with goitre, palpitations and weight loss without eye signs. Thyroid function test revealed suppressed thyroid stimulating hormone and mildly raised free thyroxine. Antithyroid globulin antibodies and antithyroid peroxidase were both strongly positive. She was initially diagnosed as Hashimoto thyroiditis in hashitoxicosis and started on carbimazole. Four months later, the patient progressed into hypothyroid state requiring thyroxine therapy for 2 years. She however became hyperthyroid again in the past 1 year. Further evaluation revealed raised TSH receptor antibodies (TRAb) and hyperfunctioning thyroid gland on Tc99m thyroid radioisotope study, leading to a revision of diagnosis to Graves’ Disease. CONCLUSION This case demonstrates Graves’ disease with alternating thyroid status poses a challenge to the patient’s diagnosis and management. Measurement of TRAb together with TSAbs and TBAbs would be helpful for diagnosis and to objectively explains the alternating thyroid function. Management includes close monitoring of thyroid function and possibly definitive therapy of radioactive iodine ablation or surgery in selected cases.